Estrutura da comunidade microbiana e a importância da bacterivoria por protozoários em uma represa subtropical (Represa do Lobo, SP, Brasil) - Mansano, Adrislaine da Silva (Universidade Federal de São Carlos, 2012)
Planktonic bacteria play important role in the organic matter decomposition, nutrient cycling and as food for organisms of higher trophic levels such as flagellates and ciliates, thus representing fundamental components in planktonic food webs. This study analyzed the microbial community structure and evaluated the importance of heterotrophic nanoflagellates (HNF) and ciliates bacterivory in a subtropical environment predominantly mesotrophic (Lobo-Broa reservoir, Brazil) by the quantification of their ingestion rates during one year period. The in situ experiments using fluorescently labelled bacteria (FLB) were conducted on the surface of two sampling points that have different trophic degrees. In parallel, physical, chemical and biological water variables were also evaluated. The ciliates showed a higher specific ingestion rate of bacteria (3,3 x 103 bact ind-1 h-1) than HNF (79,7 bact ind-1 h-1) due to differences in size and food acquisition among the two protozoans. The ingestion rates for both ciliates and HNF were always higher in the point 2 (P2) probably due to the higher water temperatures, which accelerate the protozoans metabolism, and higher bacterial densities. Concerning total protozoan bacterivory, the HNF populations had the greatest grazing impact (60%) on the reservoir bacterial community, especially the HNF smaller than 5 μm. The data showed that HNF grazing, in addition to regulation the bacteria abundance, probably also induced changes in the bacterial community structure, such as increasing bacterial filaments numbers and size. The ciliates contributed significantly to the bacterivory, especially in P2, where high densities and ingestion rates were verified. The main ciliate consumers of bacteria were from Spirotrichea, Peritrichia, Haptoria and Scuticociliatia groups. The bottom-up control was more important in the dry season and the top-down control was more important in the rainy one. Thus, in an annual basis, the resource availability and protozoan predation are equally important to the bacterial abundance regulation in the Lobo reservoir.
Keywords: Ecologia; Bactérias; Nanoflagelado; Ciliado; Mesotrófico; Grazing; Bacteria; Nanoflagellates; Ciliates; Mesotrophic; CIENCIAS BIOLOGICAS::ECOLOGIA